Determination of the 90% Effective Dose of Phenylephrine Boluses to Treat Spinal Anesthesia-Induced Hypotension in Patients with Severe Preeclampsia during Cesarean Delivery: A Pilot Study - Liu JP; Pan ZB; Zhu M; Zhu GW; Song DB; Chen XZ; Qian XW (Dove Medical Press, 2021)
Jin-Ping Liu,1 Zheng-Bin Pan,1 Miao Zhu,1 Guo-Wei Zhu,2 Da-Bing Song,2 Xin-Zhong Chen,1 Xiao-Wei Qian1 1Department of Anesthesiology, Women's Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Department of Anesthesiology, Haining Maternal and Child Health Hospital, Jiaxing, People's Republic of ChinaCorrespondence: Xiao-Wei Qian; Xin-Zhong ChenDepartment of Anesthesiology, Women's Hospital, Zhejiang University School of Medicine, Xueshi Road 1, Hangzhou, 310006, People's Republic of ChinaTel +86-571-87061501Fax +86 571 87061878Email qianxw@zju.edu.cn; chenxinz@zju.edu.cnPurpose: Treatment of spinal anesthesia-induced hypotension in patients with severe preeclampsia assumes special concern as hypotension may further reduce placental perfusion. Phenylephrine is still the first-line vasopressor for treating spinal anesthesia-induced hypotension. However, the optimal dose of phenylephrine used as intravenous (IV) boluses in patients with severe preeclampsia has not been clearly determined. We aim to calculate the 90% effective dose (ED90) of phenylephrine as IV boluses for treating spinal anesthesia-induced hypotension in patients with severe preeclampsia undergoing cesarean delivery.Patients and Methods: Forty patients with severe preeclampsia were enrolled in this prospective sequential allocation dose-finding trial. Using the biased coin up-and-down (BCUD) method, all patients in our study received an IV bolus phenylephrine of either 40, 50, 60, 70, or 80 μg when the mean arterial pressure (MAP) decreased to less than 80% of the baseline level and the ED90 was determined. The primary outcome was the success of the assigned phenylephrine bolus to maintain the MAP at or above 80% of baseline value between the induction of spinal anesthesia and delivery of the fetus. Secondary outcomes included hypertension, nausea, vomiting, bradycardia, upper sensory level of anesthesia, umbilical blood gases, and Apgar score. Estimating of the ED90 with 95% confidence interval (CI) was achieved by isotonic regression method.Results: The ED90 of phenylephrine was estimated as 62.00 μg (95% CI=50.00- 67.40 μg) using the isotonic regression method. No patients enrolled in our study experienced bradycardia and those patients who developed hypertension were all observed at the dose level 70 μg.Conclusion: For clinical practice, we recommend that phenylephrine 60 μg may be both effective and safe for treatment of spinal anesthesia-induced hypotension in severe preeclampsia during cesarean delivery.Keywords: phenylephrine, hypotension, preeclampsia, biased coin up-and-down method, ED90